Nutrient Digestibility in Pegagan Ducks Fed Diet Containing Locally Sourced Ingredients Fermented with Yeast Inoculum - Yosi , Fitra; Sandi, Sofia; Miksusanti; Rofiq, Nasir; Sutejo (International Journal of Poultry Science, 2016)
The aim of this study was to evaluate the digestibility of nutrients in the diets of Pegagan ducks fermented with a various of yeast inoculum. The yeast varieties used included tape yeast, tempe yeast and bread yeast. This study evaluated 200 female Pegagan ducks aged 2 weeks who were reared for 5 weeks. A completely randomized design (CRD) was used that consisted of 5 treatments and 4 replications. Treatment rations given were as R0 (commercial ration/control), R1 (locally sourced ration without fermentation), R2 (locally sourced ration fermented with bread yeast), R3 (locally sourced ration fermented with tape yeast) and R4 (locally sourced ration fermented with the tempe yeast). The variables observed included the digestibility coefficient of dry matter (DCDM), organic matter (DCOM), crude fiber (DCCFb), crude protein (DCCP), crude fat (DCCFt), N-free extract digestibility (NFED), nitrogen-corrected metabolizable energy (NCME) and nitrogen retention (NR). Data were analyzed using analysis of Variance (ANOVA) followed by Duncan’s multiple range test at 5%. The DCDM, DCOM, DCCFb, DCCP, DCCFt, NFED, NCME and NR values were affected by treatment (p<0.05). The DCDM, DCOM, DCCFb, DCCP, DCCFt, NFED, NCME and NR values between locally sourced ration fermented with bread yeast (R2), tape yeast (R3) and tempe yeast (R4) were not significantly different (p>0.05). The fermentation process using three types of inoculant yeast (tape yeast, tempe yeast and bread yeast) did not increase nutrient digestibility in pegagan ducks.